Prospects for transportation utility fees - Jason R. Junge; David Levinson (Journal of Transport and Land Use)
Transportation utility fees are a financing mechanism for transportation that treats the network as a utility and bills properties in proportion to their use, rather than their value as with the property tax. This connects the costs of maintaining the infrastructure more directly to the benefits received from mobility and access to the system. The fees are based on trips generated and vary with land use. This paper evaluates the fees as an alternative funding source in terms of economic, equity and administrative effects. The experiences of cities currently using utility fees for transportation are discussed. Calculations are included to determine the fee levels necessary for transportation maintenance budget needs in three sample cities and a county in the Twin Cities metropolitan area. Proposed fees for each property type are compared to current property tax contributions toward transportation. The regressive effects of the fees and the effect of adjusting for the length of trips generated are also quantified.